1984
DOI: 10.1007/bf00127264
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the abiotic degradability of organic compounds in the troposphere

Abstract: A statistically relevant correlation between the reaction rate coefficient, koH , for the OH radical reaction with 161 organic compounds in the gas phase at 300 K, and the corresponding vertical ionisation energies Ei, v, reveals two classes of compounds: aromatics where -log(koH/cm3s -1) -~ 3/2 Ei, v(eV) -2 and aliphatics where -log(7;OH/Cm 3 s-l) ~_ 4/5 El, v(eV) + 3. The prediction of the rate coefficient, koH , for the reaction of OH with organic molecules from the above equations has a probability of abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…More recent approaches to estimating (or rationalizing) H-atom abstraction rate constants by OH radicals [ 10-17~9-211 have extended this earlier method to take into account the dependence of differing C -H bond dissociation energies on the particular C -H bonds from which H-atom abstraction occurs, using literature C -H bond dissociation energies [10,15,16,20] or empirical methods [11,[12][13][14][17][18][19]211.…”
Section: Introductionmentioning
confidence: 99%
“…More recent approaches to estimating (or rationalizing) H-atom abstraction rate constants by OH radicals [ 10-17~9-211 have extended this earlier method to take into account the dependence of differing C -H bond dissociation energies on the particular C -H bonds from which H-atom abstraction occurs, using literature C -H bond dissociation energies [10,15,16,20] or empirical methods [11,[12][13][14][17][18][19]211.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of the work by Gusten et al [7] on aliphatics (n=129), the datasets to date have been limited in size and scope, and have not considered in detail the use of theoretical methods for estimating IEs within these types of models. This latter consideration is critical, as the majority of compounds for which estimated k OH values are desired have either not been synthesized experimentally, or do not have experimental IEs available in the open literature.…”
mentioning
confidence: 95%
“…Gaffney and Levin [5] found high correlation coefficients between experimental IEs and log k OH for a small set of 18 alkenes and dienes that react via hydroxyl radical addition (r=0.97, m=-0.61±0.04, b=-4.68±0.37), as well as a separate minimal set of 4 oxygenated and halogenated alkenes that also react via the addition mechanism (r=0.95, m=-0.57±0.13, -5.42±1.24). Subsequently, Gusten et al [7] reported separate aromatic and aliphatic based correlations between experimental vertical IEs and experimental -log k OH for larger sets of organic compounds: aromatics, n=32, r=0.95, s=0.29, m=1.52±0.10, b=-2.06±0.84; and aliphatics, n=129, r=0.95, s=0.36, m=0.79±0.02, b=3.06±0.24. More recently, Grosjean and Williams [12] published a correlation between the log k OH for various unsaturated organic compounds and IE (n=36, r=0.89, m=-0.44±0.04, b=-6.23±0.34), along with a separate correlation for a small subset of chlorinated olefins (n=7, r=0.81, m=1.44±0.47, b=-25.6±4.6).…”
mentioning
confidence: 97%
See 2 more Smart Citations